Thermodynamic Excess Properties and Intermolecular Interaction Using Fourier Transform Infrared for the Dodecylbenzenesulfonic Acid-Acetone Binary Liquid Mixture - Jazie, Ali A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2017)
Density, viscosity, and surface tension for the DBSA-Acetone system at the temperatures (293.15, 298.15, 301.15 K) have been investigated experimentally. Excess molar volume, viscosity deviation, surface tension deviation, and molar excess Gibbs free energy deviation are calculated at (293.15, 298.15, 301.15 K). All the non-ideal properties calculated are fitted to Redlich-Kister (RK) equation. FTIR spectrum of the DBSA-Acetone mixture have been characterized for studying the intermolecular interaction. The result of molar excess Gibbs free energy deviation and FTIR studies showed a weak hydrogen bonding for the mixture solution. While, the intramolecular interaction is strong in the case of pure DBSA and acetone due to the self-association of DBSA molecule or decreasing the dipole-dipole of acetone molecule. The result of FTIR supported the result of thermodynamic excess where the excess molar volumes were positive. The calculated values of excess molar volume are positive for all the temperatures ranging from (293.15 - 301.15 K). while, the values of viscosity deviation, surface tension deviation, and molar excess Gibbs free energy deviation are negative for all the temperatures studied.